Environmental Education through Fieldwork: Experiences from a Project Investigating Urban Water Bodies - Karthe, Daniel; Wildhage, Jan Jasper; Reeh, Tobias (Journal of Geography Education, 2012)
In a project jointly organized by a German high school and the local university's Department of Geography, students together with their teachers and scientists investigated the usage and state of water bodies in their home town (Göttingen, Germany). The environmental education impact of the project was evaluated by conducting written learner interviews prior to the project, immediately following the project work and 6 months after its completion. These were complemented by oral interviews of both the organizing scientists and teachers. Results of the evaluation revealed an increase in environmental knowledge and a sensibilization of the students for water-related environmental issues. The substantial raise in environmental awareness was only partly reflected by a modification of attitudes and willingness to act more eco-friendly. Nevertheless, it was demonstrated that a project involving scientific fieldwork can have an influence on students environmental science literacy and attitude.
Keywords: Geographic fieldwork, environmental education, water/environmental science literacy